Victoria Institute, Port-of-Spain, Trinidad, B.W.I. - (:unkn) unknown (Waterman the Hatter, Clothier and Outfitter, Trinidad, 2010)
The postcard shows the Victoria Institute which built to commemorate the Golden Jubilee of Queen’s Victoria’s reign. Fire gutted the building in 1920s and it was rebuilt in 1923, but renamed the National Museum and Art Gallery in 1965. The original building was designed by Daniel Mienerts Hahn, a German who worked in the Dept of Public Works.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Historical buildings; Port of Spain; National Museum